(3efXheI eTQhMI aj CUhd Yde GdWHs - (3eMeO Hf YeQ Hf eHGQc GdMejQj GdMVQej, HMQb , SQGL GdOjf ,J (B930 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPG JYdjb dWja Ydi fHPJi GdefXheI ai CUhd Yde GdWH JHUQI ddeHJOF hJPcQI ddefJgi GdMeO ddg GdMcje GdbGOQ GdfGaY GdVGQ GdYRjR GdbGgQ s
(3BNQgG (B:s
(3agPg cGajI PG GddH hGdage ai CUhd Yde GdWH aef MaX GdCUhd ef cd CeQ QbGHgG Edi GdhUhd Edi aQhYgG hef VY GdCUhd MQe GdhUhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B31s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3HChdg aGFOI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdeLGejYs